Experimental investigation of the effects of blank holder force and die surface angle on the warm deep drawing of AA5754-O alloy - Ozek, Cebeli; Tasdemir, Vedat (Gazi Univ, Fac Engineering Architecture, 2017)
In this study, it is aimed to determine the experimental effects of die surface angle, blank holder force and temperature on the warm deep drawing of AA5754 alloy. For this purpose, the die surfaces were machined between 0-15 degrees and the experiments were performed under 1.2 kN, 2.4 kN and 3.6 kN blank holder forces and at different temperature values, namely; room temperature (RT), 100 degrees C, 175 degrees C, and 250 degrees C. In the experiments, the die clearance, punch and die radii were kept constant as 1.35 mm and 8 mm, respectively. In order to reduce the friction force between die and blank, MoS2 was used as lubricant due to its high temperature and pressure resistance. It is experimentally found that the effects of drawing parameters were more dominant at RT and 100 degrees C. A further increase in forming temperature lead to lower forming forces, springback ratios, hardness and the more homogenous distribution of the wall thickness. It is also observed that the hardness distribution along the cup wall was tendency of increase toward the top of the cup with a significant effect of temperature.
AA 5754-O alaşiminin ilik derin çekilmesi üzerine kalip yüzey açisi ve baski plakasi kuvvetinin etkisinin deneysel araştirilmasi
Keywords: Warm deep drawing; wall thickness; die geometry; hardness distribution; springback; AA5754 alloy